Phenolic resin hard carbon as well as preparation method and application thereof

By preparing micron-scale spherical phenolic resin hard carbon in sodium ion batteries, the problem of difficulty in preparing such materials in the prior art is solved, and the high-performance sodium storage effect of sodium ion batteries is achieved.

CN119660713APending Publication Date: 2025-03-21SUZHOU PEIWA ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411900512.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The prior art is difficult to prepare micron-scale spherical phenolic resin hard carbon, which limits its application in sodium ion batteries.

Method used

Polycondensation reaction is carried out by dissolving 3-aminophenol in a specific mixed solvent, adding formaldehyde solution, and preparing phenolic resin hard carbon by pyrolysis to regulate its particle size and morphology.

Benefits of technology

Micron-scale spherical phenolic resin hard carbon was successfully prepared, which improved its sodium storage performance in sodium ion batteries and achieved high capacity, high first efficiency, high magnification and high cycle performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119660713A_ABST
    Figure CN119660713A_ABST
Patent Text Reader

Abstract

The invention discloses phenolic resin hard carbon and a preparation method and application thereof.The preparation method of the phenolic resin hard carbon comprises the following steps that S1, 3-aminophenol is dissolved in a mixed solvent to prepare a 3-aminophenol solution, and the mixed solvent is a mixed solution of 1, 6-hexanediol, 1, 4-butanediol, ethylene glycol, ethyl alcohol and water; s2, adding a formaldehyde solution into the 3-aminophenol solution, and carrying out condensation polymerization to prepare phenolic resin; and S3, performing pyrolysis on phenolic resin to prepare phenolic resin hard carbon. By adjusting the proportion of 3-aminophenol to formaldehyde, the variety and proportion of the solvent, the reaction temperature and the reaction time, the morphology and the particle size of the prepared phenolic resin microspheres can be regulated and controlled, micron-sized spherical phenolic resin is prepared, and the micron-sized spherical phenolic resin hard carbon particles have excellent sodium storage performance when being used as the negative electrode of the sodium-ion battery; high capacity, high first efficiency, high magnification and high cycle performance of the sodium ion battery are realized by preparing the phenolic resin hard carbon microspheres with proper particle size.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of carbon materials, and in particular relates to a phenolic resin hard carbon and a preparation method and application thereof. Background Art

[0002] With the vigorous development of science and technology in various industries around the world, the demand for energy in various countries has increased year by year. In recent years, the efficient use of renewable energy has become an important topic for the further development of human science and technology. In order to achieve efficient use of energy, it is necessary to develop efficient energy storage and conversion devices. Among them, the most important energy storage devices are secondary batteries of various alkali metals (including lithium-ion batteries, sodium-ion batteries and potassium-ion batteries, etc.). At present, lithium-ion battery technology has entered a development bottleneck period due to the cost issues caused by the relative scarcity of lithium resources. The reserves of sodium in the earth's crust are extremely abundant, so sodium-ion batteries are expected to replace lithium-ion batteries and become a new generation of mainstream energy storage devices.

[0003] Graphite is the most commonly used negative electrode material for lithium-ion batteries, but graphite negative electrodes are not suitable for sodium-ion batteries. Hard carbon is a type of carbon that is difficult to graphitize above 2500°C. Many studies have shown that it is suitable for use as a negative electrode material for sodium-ion batteries, and phenolic resin-based hard carbon is widely used due to its excellent thermal stability, stable structure, and low price.

[0004] The particle size, structure and morphology of phenolic resin hard carbon will affect its performance. The microsphere structure has the advantages of controllable size and shape, good structural stability and high packing density, which is suitable for negative electrode materials of batteries. However, the phenolic resin hard carbon prepared by conventional Stöber method is usually nanoscale, and it is difficult to prepare micron-scale spherical phenolic resin hard carbon. Summary of the invention

[0005] In order to overcome the above disadvantages, one of the objects of the present invention is to provide a method for preparing phenolic resin hard carbon, which can prepare micron-sized spherical phenolic resin hard carbon.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is: a method for preparing phenolic resin hard carbon, comprising the following steps: S1. Dissolving 3-aminophenol in a mixed solvent to prepare a 3-aminophenol solution, wherein the mixed solvent is a mixture of 1,6-hexanediol, 1,4-butanediol, ethylene glycol, ethanol and water; the water is preferably deionized water or purified water; S2, adding formaldehyde solution to the 3-aminophenol solution to carry out polycondensation reaction to prepare phenolic resin; S3, pyrolyzing the phenolic resin to prepare phenolic resin hard carbon.

[0007] Further, in step S1, in the mixed solvent, the volume ratio of 1,6-hexanediol, 1,4-butanediol, ethylene glycol, ethanol and water is (1-2): (1-2): (1-2): (10-20): (10-30). Exemplarily, the volume ratio of 1,6-hexanediol, 1,4-butanediol, ethylene glycol, ethanol and water is 1:1:1:10:10, 1:1:1:10:20, 1:1:1:10:30, 1:1:1:20:10, 2:2:2:10:10, 2:2:2:10:20, 2:2:2:10:30, 2:2:2:20:10 or a range consisting of any two of them.

[0008] Further, the volume ratio of ethanol to water is 1: 3 to 3: 1. Exemplarily, the volume ratio of ethanol to water is 1: 3, 1: 2, 1: 1, 2: 1, 3: 1 or a range consisting of any two thereof.

[0009] Further, in step S1, the concentration of the 3-aminophenol solution is 0.01-0.03 g / mL. Exemplarily, the concentration of the 3-aminophenol solution is 0.01 g / mL, 0.015 g / mL, 0.02 g / mL, 0.025 g / mL, 0.03 g / mL, or a range consisting of any two thereof.

[0010] Furthermore, the concentration of the 3-aminophenol solution is 0.02-0.025 g / mL.

[0011] Further, in step S2, the molar ratio of the 3-aminophenol to the formaldehyde is 1:3 to 12. Exemplarily, the molar ratio of the 3-aminophenol to the formaldehyde is 1:3, 1:5, 1:7, 1:9, 1:10, 1:12 or a range consisting of any two thereof.

[0012] Furthermore, in step S2, the molar ratio of the 3-aminophenol to the formaldehyde is 1:6-12.

[0013] Furthermore, in step S2, the reaction temperature is 75-85° C., and the reaction time is 3-5 h.

[0014] Furthermore, in step S3, the pyrolysis temperature is 600-800°C, the holding time is 2-6 h, and the heating rate is 5°C / min.

[0015] Furthermore, in step S3, the median particle size D50 of the phenolic resin hard carbon is 1-20 μm.

[0016] Furthermore, in step S3, the median particle size D50 of the phenolic resin hard carbon is 2-15 μm.

[0017] Furthermore, in step S3, the median particle size D50 of the phenolic resin hard carbon is 4-9 μm.

[0018] Furthermore, in step S3, nitrogen or argon is used as a protective gas during the high-temperature pyrolysis process.

[0019] Another object of the present invention is to provide a phenolic resin hard carbon prepared by the preparation method as described above.

[0020] The phenolic resin hard carbon as described above is used to prepare a sodium ion battery. The specific preparation steps of the sodium ion battery are: Step 1: Mix the obtained phenolic resin hard carbon negative electrode material, conductive additive and binder to prepare slurry, and use water as a dispersant. When preparing the slurry, in order to evenly mix the components, a mixer is preferably used for sufficient mixing.

[0021] Furthermore, the conductive additive is selected from one or more of carbon black, acetylene black, single-walled carbon nanotubes, multi-walled carbon nanotubes, and graphene.

[0022] Furthermore, the mass ratio of the conductive additive to the negative electrode active material is 1-10 wt%. The negative electrode active material includes a phenolic resin hard carbon negative electrode material, a conductive additive and a binder.

[0023] Furthermore, the binder is selected from at least one of sodium alginate, polyacrylic acid PAA, lithium polyacrylate LiPAA, sodium polyacrylate NaPAA, and sodium carboxymethyl cellulose CMC / styrene-butadiene rubber SBR.

[0024] Furthermore, the mass ratio of the binder to the negative electrode active material is 1-10 wt %.

[0025] Step 2: Use a coating machine to apply the obtained slurry onto a copper foil current collector with a thickness of 4-15 μm, dry it, roll it, and cut it into appropriate sizes for later use.

[0026] Step 3: The positive electrode is prepared by a slurry coating process similar to that of the negative electrode. The positive electrode material includes one or more of the following substances: a. Sodium-containing transition metal oxides, such as NaMO2 (M is one or more transition metal elements); b. Polyanion cathode materials, such as Na x M y (X a O b ) z Z w (M is a transition metal atom, X is phosphorus, sulfur or tungsten, etc., and Z is F or OH), which is connected by polyanion polyhedrons and transition metal ion polyhedrons through strong covalent bonds and has a strong and open three-dimensional network structure; c. Prussian blue / white, its chemical formula is Na x M1[M2(CN)6] (M is a transition metal atom, such as Mn, Ni, Co, Zn, Cu and Fe, etc., 0<x≤2). It is divided into two materials, Prussian white (high) and Prussian blue (low), according to the sodium ion content. It is a new technology route for sodium ion batteries. The positive electrode current collector generally uses aluminum, nickel, stainless steel, titanium, etc. or a composite foil formed by metal and non-metal. The coating dispersion solvent generally uses a non-aqueous solvent, and the adhesive generally uses a fluorine-containing polymer, such as polyvinylidene fluoride (PVDF).

[0027] Step 4: Assemble the negative electrode sheet, separator and positive electrode into a battery.

[0028] Step 5: Add electrolyte and then seal to obtain a sodium battery.

[0029] The electrolyte system is a non-aqueous electrolyte solution containing salts that is liquid at room temperature. The aprotic solvent used in the electrolyte includes at least one of dimethyl carbonate (DMC), ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), ethylene carbonate (VC), fluoroethylene carbonate (FEC), ethyl methyl carbonate (EMC), etc., and at least one sodium-containing electrolyte salt that can be dissolved in the above solvents, such as sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium perchlorate (NaClO4), etc. The concentration of the electrolyte solution is preferably 0.8~2.0 M (mole per liter). In addition, 0.1~3 wt% of a compound containing a carboxylic anhydride group, a compound containing sultones (sultone, such as propylene sultone, propane sultone, etc.) and other sulfur elements, or a compound containing boron elements, etc., can also be added to the electrolyte. The purpose is to improve the chemical stability of the electrolyte and inhibit its decomposition on the surface of the negative electrode material.

[0030] The electrolyte system may also include some or all solid electrolyte components, such as organic solid electrolytes, oxide solid electrolytes, sulfide solid electrolytes, halide solid electrolytes, etc.

[0031] The beneficial effects of the present invention are as follows: by adjusting the ratio of 3-aminophenol and formaldehyde, the type and ratio of the solvent, the reaction temperature and the reaction time, the morphology and particle size of the prepared phenolic resin microspheres can be regulated, and micron-sized spherical phenolic resins can be prepared. The micron-sized spherical phenolic resin hard carbon particles have excellent sodium storage performance as the negative electrode of the sodium ion battery. By preparing phenolic resin hard carbon microspheres with suitable particle sizes, high capacity, high initial efficiency, high rate and high cycle performance are achieved. Sodium ion batteries are expected to replace lithium ion batteries and become a new generation of mainstream energy storage devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] The drawings constituting a part of this application are used to provide a further understanding of the present invention. The illustrative embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0033] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0034] Figure 1 It is the cycle curve diagram of Example 1 and Comparative Example 1; Figure 2 is the rate performance diagram of Example 1; Figure 3 This is a SEM image of the phenolic resin hard carbon prepared in Example 1; Figure 4 This is a SEM image of the phenolic resin hard carbon prepared in Example 2; Figure 5 This is a SEM image of the phenolic resin hard carbon prepared in Example 3; Figure 6 This is a SEM image of the phenolic resin hard carbon prepared in Example 4; Figure 7 This is a SEM image of the phenolic resin hard carbon prepared in Example 5; Figure 8 This is a SEM image of the phenolic resin hard carbon prepared in Example 6; Fig. 9 This is a SEM image of the phenolic resin hard carbon prepared in Example 7; Fig.10 This is a SEM image of the phenolic resin hard carbon prepared in Example 8; Fig.11 This is a SEM image of the phenolic resin hard carbon prepared in Example 11; Fig.12 This is a SEM image of the phenolic resin hard carbon prepared in Comparative Example 1; Fig.13 This is the SEM image of the phenolic resin hard carbon prepared in Comparative Example 2; Fig.14 This is the SEM image of the phenolic resin hard carbon prepared in Comparative Example 3. DETAILED DESCRIPTION

[0035] In order to make the above-mentioned purpose, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.

[0036] Except as shown in the operating examples or otherwise indicated, all numbers used in the specification and claims to indicate the amount of ingredients, physicochemical properties, etc. are understood to be adjusted by the term "about" in all cases. Therefore, unless otherwise indicated, the numerical parameters listed in the above specification and the attached claims are approximate values, and those skilled in the art can use the teachings disclosed herein to seek to obtain the desired properties and appropriately change these approximate values. The use of numerical ranges expressed as endpoints includes all numbers within the range and any range within the range, for example, 1 to 5 includes 1, 1.1, 1.3, 1.5, 2, 2.75, 3, 3.80, 4 and 5, etc.

[0037] An embodiment of the present invention provides a method for preparing phenolic resin hard carbon, which specifically comprises the following steps: S1. Dissolving 3-aminophenol in a mixed solvent to prepare a 3-aminophenol solution, wherein the mixed solvent is a mixture of 1,6-hexanediol, 1,4-butanediol, ethylene glycol, ethanol and water.

[0038] In some embodiments, the volume ratio of 1,6-hexanediol, 1,4-butanediol, ethylene glycol, ethanol and water is (1-2):(1-2):(1-2):(10-20):(10-30).

[0039] In some embodiments, the molar ratio of the 3-aminophenol to the formaldehyde is 1:3-12.

[0040] In some embodiments, the concentration of the 3-aminophenol solution is 0.01-0.03 g / mL.

[0041] S2. Adding formaldehyde solution into 3-aminophenol solution to prepare phenolic resin.

[0042] In some embodiments, the reaction temperature is 75-85° C., and the reaction time is 3-5 h.

[0043] S3. Phenolic resin hard carbon is prepared by thermal decomposition of phenolic resin.

[0044] In some embodiments, the pyrolysis temperature is 600-800°C, the holding time is 2-6 h, and the heating rate is 5°C / min.

[0045] In some embodiments, the phenolic resin hard carbon has a median particle size D50 of 1 to 20 μm, preferably 2 to 15 μm, and more preferably 4 to 9 μm.

[0046] In some embodiments, nitrogen or argon is used as a protective gas during the high temperature pyrolysis process.

[0047] Example The following examples describe the disclosure of the present invention in more detail, and these examples are intended for illustrative purposes only, as various modifications and variations within the scope of the disclosure of the present invention will be apparent to those skilled in the art. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.

[0048] Example 1 S1. Place 5 g of 3-aminophenol in a reaction vessel containing 100 mL of deionized water, 10 mL of 1,6-hexanediol, 10 mL of 1,4-butanediol, 10 mL of ethylene glycol, and 100 mL of ethanol mixed solvent, and stir for 30 min to completely dissolve 3-aminophenol. According to calculations, the volume ratio of 1,6-hexanediol, 1,4-butanediol, ethylene glycol, ethanol, and water is 1:1:1:10:10; the concentration of 3-aminophenol solution is 5 g / (100+100+10+10+10)=0.021 g / mL.

[0049] S2. Then, 22.31 mL of 37% formaldehyde was added to the reaction system (the molar ratio of 3-aminophenol to formaldehyde was calculated to be 1:6), and the temperature was raised to 40°C to polymerize the reaction system at a stirring rate of 800 rpm for 1 h, and then the reaction temperature was raised to 75°C for 3 h.

[0050] After the reaction is completed and the suspension is cooled, the solid and liquid are separated by a centrifuge, and the solid part is washed alternately with deionized water and ethanol three times, and then dried at 80° C. to obtain a phenolic resin.

[0051] S3. The obtained phenolic resin was transferred into a corundum crucible and placed in a tubular furnace. The temperature was raised to 800°C at a rate of 5°C / min and kept at that temperature for 5 h. The temperature was then naturally lowered to obtain phenolic resin hard carbon. Nitrogen was used as a protective gas throughout the entire heating and holding process.

[0052] Example 2 This example is substantially the same as Example 1, with the main difference being that in this example, 22.31 mL of 37% formaldehyde in Example 1 is replaced with 44.62 mL of 37% formaldehyde, and after calculation, the molar ratio of 3-aminophenol to formaldehyde is 1:12.

[0053] Example 3 This embodiment is basically the same as Embodiment 1, with the main difference being that in step S2, the reaction temperature after the mixture is completely dissolved is changed from 75° C. in Embodiment 1 to 85° C.

[0054] Example 4 This embodiment is basically the same as Embodiment 1, with the main difference being that in step S3, the insulation temperature is changed from 800° C. in Embodiment 1 to 600° C.

[0055] Example 5 This embodiment is basically the same as Embodiment 1, with the main difference being that in step S3, the protective gas used is argon.

[0056] Example 6 This embodiment is basically the same as Embodiment 1, with the main difference being that in step S3, the insulation time is changed from 5 h in Embodiment 1 to 3 h.

[0057] Example 7 This comparative example is basically the same as Example 1, with the main difference that the mass of 3-aminophenol is changed from 5 g in Example 1 to 2.5 g, and the volume of 37% formaldehyde is changed from 22.31 mL in the example to 11.15 mL. After calculation, the concentration of the 3-aminophenol solution is 5 g / (100+100+10+10+10)=0.011 g / mL, and the molar ratio of 3-aminophenol to formaldehyde is 1:6.

[0058] Example 8 This embodiment is substantially the same as embodiment 1, with the main difference being that the reaction time of the phenolic resin is changed from 3 h in embodiment 1 to 24 h.

[0059] Example 9 This embodiment is basically the same as embodiment 1, and the main difference is that in step S2, 22.31 mL 37% formaldehyde in embodiment 1 is replaced with 11.15 mL 37% formaldehyde. According to calculation, the molar ratio of 3-aminophenol to formaldehyde is 1:3.

[0060] Example 10 This embodiment is basically the same as embodiment 1, except that in step S1, the volumes of 1,6-hexanediol, 1,4-butanediol and ethylene glycol are 5 mL respectively. According to calculation, the volume ratio of 1,6-hexanediol, 1,4-butanediol, ethylene glycol, ethanol and water is 1:1:1:20:20.

[0061] Embodiment 11 This embodiment is basically the same as embodiment 1, with the main difference being that in step S1, the volume of ethanol is 50 mL, the volume of deionized water is 150 mL, and the volume ratio of ethanol to water is 1:3.

[0062] Comparative Example 1 This comparative example is substantially the same as Example 1, with the main difference being that in step S1, 1,6-hexanediol, 1,4-butanediol and ethylene glycol are not added to the reaction system.

[0063] Comparative Example 2 This comparative example is basically the same as Example 1, with the main difference being that in step S1, the volume of ethanol is 150 mL, the volume of deionized water is 50 mL, and the volume ratio of ethanol to water is 1:0.33.

[0064] Comparative Example 3 This comparative example is basically the same as Example 1, with the main difference being that in step S1, the volume of ethanol is 20 mL, the volume of deionized water is 180 mL, and the volume ratio of ethanol to water is 1:9.

[0065] Experimental Example 1 The physical and chemical properties of the phenolic resin hard carbon negative electrode materials prepared in Examples 1-11 and Comparative Examples 1-3 were tested, and the test results are shown in Table 1.

[0066] Specific surface area test method: measure the amount of gas adsorbed on the solid surface at different relative pressures, and then calculate the monolayer adsorption amount of the sample based on the Brunaue-Emmett-Teller (BET formula).

[0067] Material tap density test method: The tap density is tested using the Quantachrome AutoTap tap density meter.

[0068] Table 1 Physical and chemical properties of phenolic resin hard carbon negative electrode materials of Examples 1-11 and Comparative Examples 1-3

[0069] Experimental Example 2 The phenolic resin hard carbon negative electrode materials prepared in Examples 1-11 and Comparative Examples 1-3 were used to prepare half-cells, and the electrochemical performance of the half-cells was tested. The test results are shown in Table 2.

[0070] In the half-cell, phenolic resin hard carbon negative electrode material, conductive carbon black SP, sodium carboxymethyl cellulose (CMC), and styrene-butadiene latex (SBR) are mixed in a mass ratio of 90:2:2:6 with water as a dispersant to prepare a slurry. The obtained slurry is coated on a copper foil current collector, and then dried, rolled, and cut to obtain a negative electrode sheet.

[0071] The half-cell uses metallic sodium as the negative electrode, with a voltage range of 0.005-1.5 V. During discharge, the current density is first 0.05 C constant current discharge to 0.05 V, then 0.2 C constant current discharge to 0.005 V, and then stand for 20 min, and then charge to 1.5 V with 0.05 C constant current.

[0072] Table 2: Electrochemical performance of half-cells

[0073] It can be seen from the data in Table 1 and Table 2 above that in the preparation process of the phenolic resin hard carbon provided in Comparative Examples 1-3, one or more of the parameters are not within the scope of the present invention, the particle size D50 of these phenolic resin hard carbons is relatively small (<2 μm), and the electrochemical performance of the phenolic resin hard carbon negative electrode is poor. The particle size of the phenolic resin hard carbon negative electrode material provided in Examples 1-11 of the present invention is at the micron level, and the particle size is all >2 μm. In the preferred embodiment, the particle size is in the range of 4-9 μm, and the prepared phenolic resin hard carbon negative electrode has good electrochemical performance and excellent sodium storage performance.

[0074] From the experimental data of Examples 1, 2, and 9, it can be seen that the particle size of the phenolic resin hard carbon prepared with a molar ratio of 3-aminophenol to formaldehyde of 1:3 and 1:6 is larger than the particle size of the phenolic resin hard carbon prepared with a molar ratio of 3-aminophenol to formaldehyde of 1:12, and its electrochemical performance is better. The molar ratio of 3-aminophenol to formaldehyde is preferably 1:3-6.

[0075] From the experimental data of Example 1 and Example 7, it can be seen that when the concentration of the precursor 3-aminophenol solution is 0.021 g / mL (Example 1), the experimental effect is better than that of 0.011 g / mL (Example 7), so the concentration of the precursor 3-aminophenol solution is preferably 0.020-0.025 g / mL.

[0076] From the experimental data of Example 1 and Comparative Example 1, and the attached Figure 1 It can be seen that by adding a mixed solution of 1,6-hexanediol, 1,4-butanediol and ethylene glycol to the reaction system, the three solvents can jointly adjust the physical properties of the solvent, and then the morphology and particle size of the prepared phenolic resin hard carbon microspheres can be adjusted. High capacity, high initial efficiency, high rate and high cycle performance of sodium ion batteries are achieved.

[0077] From the experimental data of Example 1, Example 11 and Comparative Example 2 and Comparative Example 3, the morphology and particle size of the prepared phenolic resin hard carbon microspheres can be regulated by adjusting the ratio of ethanol and deionized water. The particle size and electrochemical performance of the phenolic resin hard carbon prepared in Example 1 and Example 11 are better than those in Comparative Example 1, while Comparative Example 3 cannot agglomerate to form spherical phenolic resin hard carbon, so the volume ratio of deionized water and ethanol is preferably 1-3:1.

[0078] The present invention illustrates the detailed process equipment and process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process equipment and process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process equipment and process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, change of structural morphology, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

[0079] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0080] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0081] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

[0082] The above implementation modes are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing phenolic resin hard carbon, characterized in that: The following steps are involved: S1. Dissolving 3-aminophenol in a mixed solvent to prepare a 3-aminophenol solution, wherein the mixed solvent is a mixture of 1,6-hexanediol, 1,4-butanediol, ethylene glycol, ethanol and water; S2, adding formaldehyde solution to the 3-aminophenol solution to carry out polycondensation reaction to prepare phenolic resin; S3, pyrolyzing the phenolic resin to prepare phenolic resin hard carbon.

2. The method for preparing phenolic resin hard carbon according to claim 1, characterized in that: In step S1, in the mixed solvent, the volume ratio of 1,6-hexanediol, 1,4-butanediol, ethylene glycol, ethanol and water is (1-2): (1-2): (1-2): (10-20): (10-30).

3. The method for preparing phenolic resin hard carbon according to claim 1, characterized in that: In step S1, the concentration of the 3-aminophenol solution is 0.01-0.03 g / mL, preferably 0.020-0.025 g / mL; and the volume ratio of ethanol to water is 1:3-3:

1.

4. The method for preparing phenolic resin hard carbon according to claim 1, characterized in that: In step S2, the molar ratio of the 3-aminophenol to the formaldehyde is 1:3-12, preferably 1:6-12.

5. The method for preparing phenolic resin hard carbon according to claim 1, characterized in that: In step S2, the temperature of the polycondensation reaction is 75-85° C., and the reaction time is 3-5 h.

6. The method for preparing phenolic resin hard carbon according to claim 1, characterized in that: In step S3, the pyrolysis temperature is 600°C to 800°C, the holding time is 2 to 6 h, and the heating rate is 5°C / min.

7. The method for preparing phenolic resin hard carbon according to claim 1, characterized in that: In step S3, the median particle size D50 of the phenolic resin hard carbon is 1-20 μm, preferably 2-15 μm, and more preferably 4-9 μm.

8. The method for preparing phenolic resin hard carbon according to claim 1, characterized in that: In step S3, nitrogen or argon is used as a protective gas during the high-temperature pyrolysis process.

9. A phenolic resin hard carbon prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the phenolic resin hard carbon according to claim 9 in the preparation of sodium ion batteries.